2019
DOI: 10.1002/erv.2709
|View full text |Cite
|
Sign up to set email alerts
|

Altered circulating endocannabinoids in anorexia nervosa during acute and weight‐restored phases: A pilot study

Abstract: Anorexia nervosa (AN) is an eating disorder characterized by a low food intake and often exceeding exercise, leading to a particularly low body × weight proportion. Patients with AN usually report less hunger than healthy controls. Endogenous endocannabinoids (eCBs), specifically the anandamide, have been associated to hunger, as a meal initiator, but research regarding AN and eCB and inconclusive. In this pilot study, we investigated plasma levels of eCB in inpatients with AN during fasting and after eating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 35 publications
2
19
1
Order By: Relevance
“…Although a hypoactive eCB system has been stated in AN [53][54][55], describing a lower CB1R availability [56], findings related to the amount of eCBs remain still inconclusive [52,57]. Monteleone et al [52] described higher plasma AEA concentrations in AN compared with HC, whereas a recent study reported lower AEA concentrations in acute phases of the disorder and post-recovery [57], which was also supported in animal models [56]. Regarding 2-AG, studies in EDs have shown no significant differences in 2-AG concentrations when comparing BSD or AN with HC [45,52,57].…”
Section: Introductionmentioning
confidence: 99%
“…Although a hypoactive eCB system has been stated in AN [53][54][55], describing a lower CB1R availability [56], findings related to the amount of eCBs remain still inconclusive [52,57]. Monteleone et al [52] described higher plasma AEA concentrations in AN compared with HC, whereas a recent study reported lower AEA concentrations in acute phases of the disorder and post-recovery [57], which was also supported in animal models [56]. Regarding 2-AG, studies in EDs have shown no significant differences in 2-AG concentrations when comparing BSD or AN with HC [45,52,57].…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected after an 8-h fasting period, and AEA and 2-AG levels were measured. 2-AG concentrations did not differ [403]. AEA concentrations were significantly lower in AN than in the controls.…”
Section: Clinical Studiesmentioning
confidence: 55%
“…The recent pilot study by Piccolo et al (2020) [403] on patients with AN contradicts the previous studies. Piccolo et al ( 2019) sampled 15 hospitalized AN patients and nine controls.…”
Section: Clinical Studiesmentioning
confidence: 86%
“…Although there have been still no interventional studies, investigations focused on exploring the eCB system in AN have provided mixed results. While some studies comparing individuals with AN and HC reported elevated AEA concentrations in AN [14,42], other research has identi ed decreased AEA concentrations [13] or no signi cant differences [43]. These alterations in AEA concentrations observed in AN were maintained even after weight restoration [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…While some studies comparing individuals with AN and HC reported elevated AEA concentrations in AN [14,42], other research has identi ed decreased AEA concentrations [13] or no signi cant differences [43]. These alterations in AEA concentrations observed in AN were maintained even after weight restoration [13,14]. Regarding 2-AG, most studies have found no signi cant differences comparing patients with AN and HC [13,14,42,43].…”
Section: Introductionmentioning
confidence: 99%